2016
DOI: 10.1525/sod.2016.2.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Remittances

Abstract: Young, tertiary-edu ated e ig a ts see the sel es, a d a e see thei ho e ou t s government, as agents of economic and social change, especially if they can be incentivized to return home. In this paper we examine whether this hypothesized positive impact is realized, taking the case of Latvia, a small peripheral country in north-east Europe, formerly part of the Soviet Union but since 2004 a member-state of the European Union. We build our analysis on data from an online questionnaire (n=307) and from narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In the case of Poland, Klein-Hitpaß (2016) found that by transferring organisational knowledge, highly skilled return migrants initiated institutional change, which was especially valuable to support the transformation from a socialist planned economy to a democratic market economy. On the other hand, a study on returning Latvian graduates revealed that the wish to act as 'agent of change' back home is often constrained by the limited scale of the market and recruitment practices that lack transparency (King et al, 2016). These findings point to the strong interrelations between cultural and social capital in the context of transnational flows of knowledge but also to the relevance of institutional contexts for an effective implementation of knowledge.…”
Section: Student Mobility and Transnational Flows Of Knowledgementioning
confidence: 99%
“…In the case of Poland, Klein-Hitpaß (2016) found that by transferring organisational knowledge, highly skilled return migrants initiated institutional change, which was especially valuable to support the transformation from a socialist planned economy to a democratic market economy. On the other hand, a study on returning Latvian graduates revealed that the wish to act as 'agent of change' back home is often constrained by the limited scale of the market and recruitment practices that lack transparency (King et al, 2016). These findings point to the strong interrelations between cultural and social capital in the context of transnational flows of knowledge but also to the relevance of institutional contexts for an effective implementation of knowledge.…”
Section: Student Mobility and Transnational Flows Of Knowledgementioning
confidence: 99%
“…Social remittance refers to the “ideas, behaviors, identities, and social capital that flow from receiving‐ to sending‐country communities” (Levitt, 1998, p. 926). Knowledge transfer is a form of social remittance from migrants abroad, which means the flow of knowledge, skills, ideas, and practices to the home countries (King, Lulle, & Buzinska, 2016). Conversely, only highly‐skilled migrants, who have worked abroad and accumulated human capital, share their learning with local industries when they return to their home countries (Nyberg–Sørensen, Van Hear, & Engberg–Pedersen, 2002, p. 23).…”
Section: The Migration‐development Nexus and Nurse Migration: Develop...mentioning
confidence: 99%